Prime Minister's Decree No. 2140 of the year 2023 Amending Certain Provisions of the Executive Regulations of the Investment Law Issued by Prime Minister’s Decree No. 2310 of the Year 2017 = قرار رئيس مجلس الوزراء رقم 2140 لسنة 2023 بتعديل بعض أحكام اللائحة التنفيذية لقانون الاستثمار الصادرة بقرار رئيس مجلس الوزراء رقم 2310 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic